PHYSICAL DEVELOPMENT INDEX METHOD ASSESSMENT OF IRKUTSK PRESCHOOL AGE CHILDREN - I. A. Kirilova (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
189 preschool age children (3-6 y.o.) of Irkutsk have been surveyed. By means of a centile method all the surveyed children have been divided into three groups according to their physical development (PD): the 1st group - children with harmonious PD, the 2nd group - children with disharmonious PD due to body weight deficiency, the 3rd group - children with disharmonious Pd due to body weight surplus. Results of research revealed PD deterioration, which was expressed in body weight increase in children of 3-6 years of age. Index method PD assessment showed that calculations received with this method do not correspond with groups of harmony of preschool children physical development.